DAMPAK ALIH FUNGSI LAHAN TERHADAP KEHIDUPAN SOSIAL EKONOMI MAYARAKAT DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Riswanto, Nanang; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Conversion of agricultural land could be interpreted as a change in land use from its original function. Rice field in the village of Rambah Baru converted to be oil palm plantations. Conversion of the agricultural land of rice fields into palm oil plantations, followed by the shift of the livelihoods of farmers in the village of Rambah Baru from rice farmers into oil palm farmers. The livelihood also closely related to the economic aspects and changes in the economic aspects will also affect the social conditions of society, so that the conversion of agricultural land of rice fields also have an impact on socio-economic conditions of the people in the village of New Rambah. The focus of this research is to determine the causes of the conversion of agricultural land of rice fields into oil palm plantations and land conversion impacts on socio-economic life of society in the village of Rambah Baru.This research was conducted in the Rambah Baru village, Rambah Samo district, Rokan Hulu regency. The method used in this research is descriptive method with quantitative approach. Sources of data obtained from observation, interviews, documentation and questionnaires with farmers as key informants which amount is 30 people who convert their land, 30 people who did not convert their land functioned as proponent informants and key informants totaling 6 people.The results showed the causes of agricultural land conversion of rice fields into palm oil plantations are caused by external factors and internal factors. External factors include damage to irrigation, sources of public knowledge,environments which were changed, and government policies. In addition, the conversion of agricultural land in the village of New Rambah also occur because it is caused by internal factors include the monthly income of farmers, farmers' age, education level, number of dependents, and the degree of dependence on the land. Conversion of the agricultural land of rice fields into palm oil plantations had a positive impact on the socio-economic life of society in the village of Rambah Baru.Keywords : land conversion, social change, socio-economic conditions .